Exports, Foreign Market Structure, and Profitability in Japanese and U.S Manufacturing - Yamawaki, Hideki (The Review of Economics and Statistics, 1986)
This paper examines the influence of price d ecisions by foreign firms on export price decisions by domestic firms. The theor etical analysis develops a general model which hypothesizes a positive relation between export price and foreign price assuming international product differenti ation. This model further suggests that export price depends on foreign structur al traits as they determine foreign price. The empirical analysis, based on a cr oss- section of sixty-nine four-digit manufacturing industries matched between th e United States and Japan, provided support for the hypothesis that foreign mark et structure and foreign pricing affect export pricing and thus the observed pri ce-cost margin. Copyright 1986 by MIT Press.